A Tecnologia no universo infantil: um olhar sobre a mediação da aprendizagem. - Oliveira, Polyana Alves de (Universidade Federal do Tocantins, 2020)
The purpose of this study was to investigate how the process of learning of children in the technological era in two Tocantinópolis-Tocantins Schools, both public, attending nursery and pre-school follow-up. The methodology for the search of information used two aspects: bibliographic and field research. Starting from Piaget's studies, in his approach to the developmental phases of child intelligence, emphasis is placed on the first two stages, since it is the stage in which children are in Early Childhood Education. As consequence, the field research was carried out in two schools of the municipal network, one which is a nursery school and another preschool, where the observations of the classes were carried out, in order to ascertain the place of the technological apparatuses in the process of teaching and learning of the children so small. The results of the research show that the schools observed were quite fragile in terms of the use of digital technological resources and did not present any school program or project that influenced or made use of new technologies for this phase.